Effect of Nurse-led Telephone Follow ups (Tele-Nursing) on Diet Adherence among Type 2 Diabetic Patients - M Zakerimoghadam; SH Bassampour; A Rjab; S Faghihzadeh; M Nesari (Tehran University of Medical Sciences, 2008)
Background & Aim: Diabetes education does not assure adherence to diabetic regimen. The aim of this study was to investigate the effect of nurse-led telephone follow ups (Tele-Nursing) program on adherence to diabetic diet among type 2 diabetic patients. Methods & Materials: This was a quasi experimental study. Sixty patients who were registered at Iranian Diabetes Society were selected using convenience sampling method. Data gathering instruments included a data sheet to record glycosylated hemoglobin and a questionnaire. Data were gathered at baseline and 12 weeks after the intervention. First, all participants attended in a three-day self-care education and dietary consultation program at Iranian Diabetes Society. Then, they were randomly assigned to the experiment and control groups. Telephone follow ups were applied in experiment group for 3 months, twice a week for the first month and then weekly for the second and third months. Data were analyzed using SPSS version 13. Results: Results showed that there were significant statistical differences between control and experiment groups in adherence to diabetic diet (P=0.035). There were significant differences in glycosylated hemoglobin between control and experiment groups after the intervention (P<0.000). Conclusion: According to the results of the study, it is concluded that the nurse-led telephone follow ups can improve HbA1c and diet adherence in type 2 diabetic patients.